2013
DOI: 10.3174/ajnr.a3498
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Spaces Are Associated with Atherosclerosis: An Insight from the Northern Manhattan Study

Abstract: Background and Purpose Perivascular spaces are potential spaces found between brain blood vessels and surrounding leptomeninges that have been associated with cardiovascular risk factors and dementia, but less is known about their relationship to atherosclerosis. We tested the hypothesis that perivascular spaces are associated with atherosclerosis. Materials and Methods Participants from the Northern Manhattan Study who remained stroke-free were invited to participate in an MR imaging substudy. Parenchymal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 28 publications
13
102
5
Order By: Relevance
“…Scan acquisition and rating methods vary across studies, which may explain the differences in observations across previous studies on PVS. Age, for example, was not related to PVS ratings in all studies, 10,11 and, in some studies, age was only related to BG but not to CSO PVS, [12][13][14] while in other studies the opposite was found. 15,16 Microscopically, PVS are highly prevalent throughout the healthy brain, which means that their visibility on MRI will probably increase when image resolution increases.…”
Section: Introductionmentioning
confidence: 74%
“…Scan acquisition and rating methods vary across studies, which may explain the differences in observations across previous studies on PVS. Age, for example, was not related to PVS ratings in all studies, 10,11 and, in some studies, age was only related to BG but not to CSO PVS, [12][13][14] while in other studies the opposite was found. 15,16 Microscopically, PVS are highly prevalent throughout the healthy brain, which means that their visibility on MRI will probably increase when image resolution increases.…”
Section: Introductionmentioning
confidence: 74%
“…12 We found a slight increase in the global score for PVS number with advancing age, which is in accordance with most other studies. 4,8,9,13,[28][29][30][31] Our study sample was relatively healthy, 20 which might partly explain a smaller increase with age than expected, because PVS are presumably correlated with the degree of cerebral small-vessel disease and amyloid deposition with increasing age. 17,18 We did not find a sex difference in the distribution of PVS, even though it has been reported in earlier studies 11,13,16 ; notably, one of these studies comprised a very large population-based sample (n ϭ ϳ1800), in which men were found to have more PVS in the basal ganglia than women, 13 while another large-scale study of patients with ischemic stroke (n ϭ 1090) found that men had more PVS in the white matter than women, but there was no sex difference in the distribution of PVS in the basal ganglia.…”
Section: Discussionmentioning
confidence: 97%
“…To date, only very few studies have had such a large sample of community dwellers. 4,13,29 In addition, because our scale is based on counting the number and measuring the diameter of PVS, it can be used on different MR imaging sequences, as opposed to the visual impression-based rating scales. Furthermore, the regionalization in the assessments of both PVS and WMH is of relevance when studying their correlations with vascular risk factors and cognitive aging.…”
Section: Discussionmentioning
confidence: 99%
“…15 We compared demographic, clinical, and imaging characteristics of CAA patients with high versus low CSO-PVS degree using appropriate univariable tests: χ 2 test or Fisher exact test for categorical variables and Student t test for age. Multivariable logistic regression analysis was used to explore the relation between high CSO-PVS degree and cSS adjusted for other variables based on the results of univariable analysis, plus other biologically plausible confounders related to PVS [18][19][20][21][22] or CAA severity, including age, sex, hypertension, WMH, CMB number, and previous history of symptomatic ICH (see Results section of this article). We further adjusted our multivariable model for possible or probable CAA diagnostic category.…”
Section: Resultsmentioning
confidence: 99%